NARAJUANG:: Diorama Of Struggle Of November 10, 1945 Based On Augmented Reality To Develop Digital Literacy - Fajriyah, Izzatul; Muhammad Ega Firmansyah; Abimanyu, Satria Febri Putra; Erma Nur Jannah; Syahrani Granita Putri Nadwan; Afsari Indah Moekti (Universitas Negeri Surabaya, 2025)
This study aims to develop a history learning media based on Augmented Reality (AR) technology entitled NaraJuang: The 10 November 1945 Struggle Diorama to improve students' digital literacy and strengthen nationalism values. The research employed a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The developed product is a digital diorama application featuring interactive historical content, three-dimensional visualization, audio narration, and user-driven exploration. Expert evaluation indicated that the media met feasibility requirements, and its implementation demonstrated improvements in digital literacy competencies, learning motivation, student engagement, and historical understanding. The use of immersive visualization and interactive narration encouraged learners to construct meaning, reflect on historical context, and recognize the relevance of national heritage in the digital era. This finding highlights the potential of AR-based media to support higher-order thinking skills, particularly in history learning, where contextualization, interpretation, and emotional connection are essential. The study concludes that NaraJuang serves as an effective and innovative learning media that is contextual, interactive, and aligned with twenty-first-century educational demands.